Cambits: A Reconfigurable Camera System. - MAKOTO ODAMAKI; NAYAR, SHREE K. (Communications of the ACM, 2017)
The authors discuss research conducted at the Columbia University Vision Laboratory concerning the development of a modular imaging system known as Cambits. According to the article, the system can be utilized for computational photography, is designed to be a scalable open platform, and permits users to add hardware blocks and computational photography algorithms.